Lexical variations of Minangkabau language within West Sumatra and Peninsular Malaysia: a dialectological study - Reniwati,; Midawati,; Noviatri, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Minangkabau people have a long history of migrating overseas especially to Peninsular Malaysia. They migrated to overseas with their soul, original culture and language. This study attempted to trace the Minangkabau of the language’s aspects, in particular, lexical aspect by using the theory in dialectology. For grouping variations of language is used the dialektometri’s method. Within the framework of solving the problem of research, there are three stages of the method used: 1) the stage providing data; 2) the stage analysing data; and 3) the stage presenting the analysis results. The population of this study was the whole speech Minangkabau society in the area of origin (Kabupten 50 Kota and Kabupaten Tanah Datar) and in the overseas area (Negeri Sembilan, Melaka and Pahang). The sample was speech Minangkabau society in Nagari Koto Baru Simalanggang and Nagari Rao-Rao. The sample in the overseas area is a region of Rembau, Naning and Kuantan. After being done the comparison, the fourth samples show the lexical similarities and lexical differences. However, the calculation of dialecttometric method is not indicating the degree of variation at the languages and dialects level. It is only at the subdialect and different talk level. The lexical differences in overseas areas show that there has been a change. The change was caused by lingual factors and nonlingual factors.